Bilateral inverse canine impaction: a case report - Tzu-Yuan Weng; Shiuan-Hui Wang; Chih-Cheng Chen; Lih-Jyh Fuh; Ke-Hung Liu; Jui-Ting Hsu (Journal of Medical Case Reports)
Abstract Background Maxillary canine impaction can result in malocclusion, temporomandibular joint complications, and esthetic concerns, thus influencing craniofacial development. Although cases of impacted canines are not uncommon in clinical practice, the likelihood of simultaneous bilateral impaction is extremely low; very few reports have documented cases of bilaterally symmetrical, inversely impacted canines. Case presentation This paper reports a rare case of maxillary canine impaction, a condition characterized by the abnormal eruption of teeth. Potential causes of this condition include genetic, systemic, and localized factors. We analyzed this condition in the skeletal remains of a Taiwanese girl aged 11–14 years. The skeleton, dating 440–598 AD, was recovered from central Taiwan in 2019. Through panoramic X-ray and dental cone-beam computed tomography, we constructed a three-dimensional model of the skull, which exhibited bilateral symmetrical, inversely impacted maxillary canines—a rare clinical observation. On the basis of the current understanding of the dental field, the treatment of maxillary canine impaction is time consuming and labor intensive. Different impacted canine teeth have different difficulty levels of treatment. Conclusion The archaeological data in this article show that 1500 years ago humans already had the problem of impacted canine teeth in the upper jaw. Moreover, bilaterally symmetrical maxillary canine impaction is very rare in clinical cases.